Application of Expected Loss (EL) for Loan Loss Estimation Based on Loan Term Using Simulation Data - Tenripada, Andi Sakinah Yan (Communication In Research And Publications, 2025)
This study aims to evaluate the effect of loan tenor on loan loss estimation using the Expected Loss (EL) model. Through this simulation data calculation, various scenarios with varying loan tenors show that loan tenors have a significant influence on the calculation of Expected Loss (EL). Longer tenors tend to increase the Expected Loss (EL) due to an increase in credit risk over time. The calculation results provide important implications for financial institutions in setting lending policies and managing credit risk.